Implementation of Integrated Stunting Prevention Policy in Gresik Regency - Yasmin Nur Kholisa; Indira Arundinasari; Elisa Pingky Vernanda; Julia Afianti; Adelia Putri Utami; Sae Dila Yanuansyah (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Stunting is a manifestation of growth failure that begins in the first 1000 days of birth. To overcome this problem, the Gresik Regency Government issued regent regulation Number 9 of 2023 regarding the Acceleration of Reducing Integrated Stunting as an effort to prevent and reduce stunting rates in Gresik Regency. Driyorejo District is an area with a fairly high number of stunting cases in Gresik Regency. This research aims to analyze how the integrated stunting reduction acceleration policy is implemented in Driyorejo District, Gresik Regency. The research method used is descriptive qualitative research method. Data collection using interview, documentation and observation methods. This research is based on the implementation theory according to Edward III which is influenced by 4 variables, namely bureaucratic structure, communication, resources and disposition. The results of the research explain that the communication process is carried out through coordination meetings which aim to discuss the implementation of stunting prevention so that it can run optimally. . All human resources work together and material resources are also needed to reduce the stunting rate. Apart from that, other supporting factors such as SOPs and fragmentation in carrying out their roles and responsibilities are carried out with coordination which is an element in the bureaucratic structure and the policy implementers in reducing integrated stunting prevention at the Driyorejo Community Health Center have integrated human resources related to stunting prevention.